Penerapan Model Rais-Mr3 dalam Tata Kelola Transportasi Andalan di Sulawesi Selatan - Sirajuddin Sirajuddin; Muhammad Rais Rahmat Razak; Haeruddin Syarifuddin (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the effect of implementing the Rais-MR3 Model on the effectiveness of